CFTR chloride channel as a molecular target of anthraquinone compounds in herbal laxatives - Yang Hong; Xu Li-na; He Cheng-yan; Liu Xin; Fang Rou-yu; Ma Tong-hui (Acta Pharmacologica Sinica, 2016)
Aim: To clarify whether CFTR is a molecular target of intestinal fluid secretion caused by the anthraquinone compounds from laxative herbal plants. Methods: A cell-based fluorescent assay to measure I− influx through CFTR chloride channel. A short-circuit current assay to measure transcellular Cl−current across single layer FRT cells and freshly isolated colon mucosa. A closed loop experiment to measure colon fluid secretion in vivo. Results: Anthraquinone compounds rhein, aloe-emodin and 1,8-dihydroxyanthraquinone (DHAN) stimulated I− influx through CFTR chloride channel in a dose-dependent manner in the presence of physiological concentration of cAMP. In the short-circuit current assay, the three compound enhanced Cl− currents in epithelia formed by CFTR-expressing FRT cells with EC50 values of 73±1.4, 56±1.7, and 50±0.5μmol/L, respectively, and Rhein also enhanced Cl− current in freshly isolated rat colonic mucosa with a similar potency. These effects were completely reversed by the CFTR selective blocker CFTRinh-172. In in vivo closed loop experiments, rhein 2 mmol/L stimulated colonic fluid accumulation that was largely blocked by CFTRinh-172. The anthraquinone compounds did not elevate cAMP level in cultured FRT cells and rat colonic mucosa, suggesting a direct effect on CFTR activity. Conclusion: Natural anthraquinone compounds in vegetable laxative drugs are CFTR potentiators that stimulated colonic chloride and fluid secretion. Thus CFTR chloride channel is a molecular target of vegetable laxative drugs.